The Role of Mammographic Breast Area/Microcalcification Cluster Area (BA/MCA) Ratio in the Classification of BI-RADS 4 Lesions: A Step for Development of Artificial Intelligence in Breast Cancer Patients - Ibrahim Burak Bahçecioğlu; Şevket Barış Morkavuk; Şebnem Çimen; Müjdat Turan; Gökay Çetinkaya; Mehmet Ali Gülçelik (International Journal of Clinical Practice, 2024)
Conclusion: The increase in the ratio of MCA to BA might have a place in the differentiation of BI-RADS 4 lesions. We foresee that artificial intelligence could also have a place in the classification of BI-RADS lesions with software to be installed on the mammography computer.